Small extracellular vesicles derived from mesenchymal stem cell facilitate functional recovery in spinal cord injury by activating neural stem cells via the ERK1/2 pathway - Hu, Xinyuan; Liu, Zhong; Zhou, Xinru; Jin, Qian; Xu, Wenrong; Zhai, Xiao; Fu, Qiang; Qian, Hui (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury (SCI) causes severe neurological dysfunction leading to a devastating disease of the central nervous system that is associated with high rates of disability and mortality. Small extracellular vesicles (sEVs) derived from human umbilical cord mesenchymal stem cells (hucMSC-sEVs) have been explored as a promising strategy for treating SCI. In this study, we investigated the therapeutic effects of the intralesional administration of hucMSC-sEVs after SCI and determined the potential mechanisms of successful repair by hucMSC-sEVs. In vivo, we established the rat model of SCI. The Basso, Beattie, Bresnahan (BBB) scores showed that hucMSC-sEVs dramatically promoted the recovery of spinal cord function. The results of the hematoxylin–eosin (HE) staining, Enzyme-Linked Immunosorbent Assay (ELISA), and immunohistochemistry showed that hucMSC-sEVs inhibited inflammation and the activation of glia, and promoted neurogenesis. Furthermore, we studied the effect of hucMSC-sEVs on neural stem cells(NSCs) in vitro. We found that hucMSC-sEVs did not improve the migration ability of NSCs, but promoted NSCs to proliferate and differentiate via the ERK1/2 signaling pathway. Collectively, these findings suggested that hucMSC-sEVs promoted the functional recovery of SCI by activating neural stem cells via the ERK1/2 pathway and may provide a new perspective and therapeutic strategy for the clinical application of hucMSC-sEVs in SCI treatment.